Gully rehabilitation in southern Ethiopia – value and impacts for farmers - Mekuria, Wolde; Phimister, E.; Yakob, G.; Tegegne, Desalegn; Moges, A.; Tesfaye, Y.; Melaku, Dagmawi; Gerber, C.; Hallett, P. D.; Smith, J. U. (Copernicus GmbH, 2024)
Gully erosion can be combatted in severely affected regions like sub-Saharan Africa using various low-cost interventions that are accessible to affected farmers. For successful implementation, however, biophysical evidence of intervention effectiveness needs to be validated against the interests and priorities of local communities. Working with farmers in a watershed in southern Ethiopia, we investigated (a) the effectiveness of low-cost gully rehabilitation measures to reduce soil loss and upward expansion of gully heads; (b) how farmers and communities view gully interventions; and (c) whether involving farmers in on-farm field trials to demonstrate gully interventions improves uptake, knowledge, and perceptions of their capacity to act. On-farm field experiments, key-informant interviews, focus group discussions, and household surveys were used to collect and analyse data. Three gully treatments were explored, all with riprap, one with grass planting, and one with grass planting and check-dam integration. Over a period of 26 months, these low-cost practices ceased measurable gully head expansion, whereas untreated gullies had a mean upward expansion of 671 cm, resulting in a calculated soil loss of 11.0 t. Farmers had a positive view of all gully rehabilitation measures explored. Ongoing rehabilitation activities and on-farm trials influenced the knowledge and understanding of similar gully treatments among survey respondents. On-farm experiments and field day demonstrations empowered farmers to act, addressing pessimism from some respondents about their capacity to do so.